TRANSFORMASI EKONOMI PARIWISAATA MELALUI KECERDASAN ARTIFISIAL DAN PLATFORM DIGITAL: STUDI MOBILITAS SOSIAL MASYARAKAT DI KABUPATEN BONDOWOSO - Sri Wahyuni; Siti Noor Aini (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
This study examines the role of artificial intelligence (AI) and digital platforms in supporting tourism economic transformation and social mobility in Bondowoso Regency, Indonesia. The rapid development of digital technology has significantly influenced tourism activities by changing patterns of promotion, service delivery, and market access for local communities. In Bondowoso, tourism development has increasingly contributed to economic diversification, particularly through nature-based tourism, agro-tourism, and community-based tourism activities. However, the integration of AI and digital technology remains uneven due to differences in digital literacy, infrastructure, and local adaptive capacity. This research employs a mixed-methods approach by integrating qualitative field research and the Analytic Hierarchy Process (AHP). Data were collected through field observation, in-depth interviews, focus group discussions, and structured questionnaires involving tourism actors, small business owners, and local stakeholders. The AHP method was used to identify priority factors influencing tourism digital transformation. The findings indicate that digital literacy is the most influential factor in tourism economic transformation, followed by digital infrastructure, AI utilization, policy support, and stakeholder collaboration. Digital platforms have enabled local communities to expand tourism promotion, increase market access, and create alternative sources of income, thereby contributing to social mobility. Although AI adoption remains at an early stage, its presence has begun to support tourism marketing efficiency and digital communication. The study concludes that tourism digital transformation in Bondowoso requires strengthening human resource capacity, improving digital infrastructure, and promoting context-based technological innovation to ensure inclusive and sustainable local economic development.